Edukasi Perkembangan Emosi dan Kepribadian untuk Kesehatan Mental Remaja - Jumaini, Jumaini; Clarisa, Afdwi; Nafsah, Dzikriyatin; Farza, Fadhilah; Sari, Fitri Sekar; Mardhotilah, Fitria; Hadini, Hikmatul; Saragih, Iin Rismawati; Tilla, Marda; Sari, Mudrikah; Hanifa, Ummu (Universitas Pahlawan Tuanku Tambusai, 2025)
Adolescence is a crucial transitional phase characterized by physical, psychological, and emotional changes. With the increasing number of adolescents in Indonesia, attention to their mental and emotional health has become essential. This study aims to provide education on personality and emotional development to 21 adolescents in RW 05, Rumbai Bukit. The activity was conducted through health counselling that included pre-tests and post-tests to measure the participants' knowledge improvement. Analysis results indicated that the average knowledge score of adolescents increased from 6.9 to 7.4 after the education session, with a significant improvement of 0.5 points. The material was delivered through various methods, including presentations, videos, and leaflets, which proved effective in enhancing participants' enthusiasm and positive responses.